Peace Education, Attentive Creativity and Sustainable Development - Sonia París Albert (Universidad Autónoma de Madrid, 2019)
Current societies demand a greater commitment to Peace Education. Using pedagogical methodologies alternative to the classic narratives of teachers, with which students' active participation is promoted as well as their ethical, critical and creative thinking, this text claims a greater cultivation of Peace Education, which should also make possible the reflection on contents that go beyond the classic curricula and that are related, for example, to sustainable development. In this sense, Peace Education is conceived as a fundamental tool for the achievement of the Sustainable Development Goals that are set out in the Agenda 2030. A Peace Education that demands, in a very special way, the cultivation of an attentive creativity to approach the issues related to the sustainable development and, therefore, the construction, establishment and maintenance of creative peace(s) for a sustainable development. The priority of attentive creativity in Peace Education is approached, here also, from everydayness and simplicity, and from recognition to the features of intersubjectivity and performativity as two of its essential attributes.